Optimalisasi Laba Berdasarkan Optimalisasi Harga Jual Produk Pelaku UMKM - Ruswan Nurmadi; Liza Novietta; Kersna Minan (Jurnal Pengabdian Kepada Masyarakat Digital, 2023)
After the initial assistance regarding the importance of calculating the cost of production and cost of sales to optimize the selling price of MSME products, the next step is assistance regarding the process of calculating and determining product selling prices so that profit optimization can be achieved. MSMEs are also given socialization regarding the importance of obtaining optimal profits. If the profit earned increases, then the optimization of the selling price is declared successful. Of course, this is what SMEs want. The savings made when optimizing product selling prices can be used by MSME actors for other things needed in their business operations. By determining the optimal product selling price, MSME players will also get optimal profit. Forum Akademisi dan Praktisi Desa (FAPDes), in which Universitas Harapan Medan is one of the Higher Education Institutions that has joined, has carried out activities in the Village Excellence Product Assistance Program conducted by MSME actors. Through the observations that have been made, in fact, MSME actors have obtained increased profits based on optimal product selling prices. However, MSME actors feel that the increase in profit is not optimal and requires further periodic assistance so that their business can survive, develop, or compete with similar businesses.Keywords: MSMEs, Selling Price, Profit